2018
DOI: 10.1038/s41598-018-33354-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel acetylcholinesterase inhibitors designed by pharmacophore-based virtual screening, molecular docking and bioassay

Abstract: In this study, pharmacophore based 3D QSAR models for human acetylcholinesterase (AChE) inhibitors were generated, with good significance, statistical values (r2training = 0.73) and predictability (q2training = 0.67). It was further validated by three methods (Fischer’s test, decoy set and Güner-Henry scoring method) to show that the models can be used to predict the biological activities of compounds without costly and time-consuming synthesis. The criteria for virtual screening were also validated by testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 76 publications
(86 reference statements)
4
70
0
Order By: Relevance
“…For example, amino acids Trp 82 , Tyr 332 , and His 438 from BuChE are equivalent to Trp 86 , Tyr 341 , and His 447 from AChE in terms of interactions with the ligand. The results of molecular docking studies are in line with formerly published findings (Bajda et al, ; Darras et al, ; Jang et al, ; Lazewska et al, ; Morini et al, ). In addition, the results of binding affinity prediction for the complexes of ligand‐cholinesterase are consistent with the experimentally determined anticholinesterase activity of compounds 3 and 4 .…”
Section: Discussionsupporting
confidence: 90%
“…For example, amino acids Trp 82 , Tyr 332 , and His 438 from BuChE are equivalent to Trp 86 , Tyr 341 , and His 447 from AChE in terms of interactions with the ligand. The results of molecular docking studies are in line with formerly published findings (Bajda et al, ; Darras et al, ; Jang et al, ; Lazewska et al, ; Morini et al, ). In addition, the results of binding affinity prediction for the complexes of ligand‐cholinesterase are consistent with the experimentally determined anticholinesterase activity of compounds 3 and 4 .…”
Section: Discussionsupporting
confidence: 90%
“…The GH score ranges between 0 and 1 and indicates null and ideal models, respectively. Pharmacophore model with GH score higher than 0.70 is considered as valid model for virtual screening of large databases [ 31 , 32 ]. The enrichment factor (EF) determines the specificity and selectivity of the model to identify active compounds during the screening of decoy test set.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies dealing with the application of the parallel strategy in the search of novel hits have been reported in the last years [ 118 , 119 , 120 , 121 ]. An illustrative example is the work by Vucicevic et al [ 119 ], who reported the identification of compounds with anticancer potential effects through a parallel LB and SB screening protocol ( Figure 4 A).…”
Section: Parallel Lb and Sb Approachesmentioning
confidence: 99%